The imprinted region on human chromosome 7q32 extends to the carboxypeptidase A gene cluster: an imprinted candidate for Silver-Russell syndrome. Issue 4 (1st April 2003) - Bentley, L; Nakabayashi, K; Monk, D; Beechey, C; Peters, J; Birjandi, Z; Khayat, F E; Patel, M; Preece, M A; Stanier, P; Scherer, S W; Moore, G E
Abstract : Imprinted gene(s) on human chromosome 7q32-qter have been postulated to be involved in intrauterine growth restriction associated with Silver-Russell syndrome (SRS) as 7–10% of patients have mUPD(7). Three imprinted genes, MEST, MESTIT1, and COPG2IT1 on chromosome 7q32, are unlikely to cause SRS since epigenetic and sequence mutation analyses have not shown any changes. One hundred kilobases proximal to MEST lies a group of four carboxypeptidase A ( CPA ) genes. Since most imprinted genes are found in clusters, this study focuses on analysing these CPA s for imprinting effects based on their proximity to an established imprinted domain. Firstly, a replication timing study across 7q32 showed that an extensive genomic region including the CPA s, MEST, MESTIT1, and COPG2IT1 replicates asynchronously. Subsequently, SNP analysis by sequencing RT-PCR products of CPA1, CPA2, CPA4, and CPA5 indicated preferential expression of CPA4 . Pyrosequencing was used as a quantitative approach, which confirmed predominantly preferential expression of the maternal allele and biallelic expression in brain. CPA5 expression levels were too low to allow reliable evaluation of allelic expression, while CPA1 and CPA2 both showed biallelic expression. CPA4 was the only gene from this family in which an imprinting effect was shown despite the location of this family of genes next to an imprinted cluster. As CPA4 has a potential role in cell proliferation and differentiation, two preferentially expressed copies in mUPD patients with SRS syndrome would result in excess expression and could alter the growth profiles of these subjects and give rise to intrauterine growth restriction.